Gut microbiome diversity as adjuvant marker for immune function - Mahdaleny; Febriana Catur Iswanti (Acta Biochimica Indonesiana, 2022)
The gastrointestinal (GI) tract represents our most intimate contact with the external environment. The GI tract responsible for extracting the appropriate nutrients we need to thrive, maintaining an appropriate balance of helpful and harmful microbes, and acting as a conduit for waste removal. In essence, the extracellular matrix of gut mucosal biofilm is a complex network of microbes and their secretions, as well as the host's secretions and signals (mainly mucus/mucin). Mucin, bacterial polysaccharides, and protein combine to form a unique mucosal biofilm that serves as a home for a variety of commensal and pathogenic organisms in the host. Maintaining proper mucosal barrier function is vital for both GI and systemic health. The lumen of the gut contains numerous entities that should never reach the bloodstream or lymphatic system. The mucosal barrier's integrity is maintained by a single layer of tightly fitted columnar epithelial, and more than 70% of the immune system components are closely associated with the GI tract.